Integration of river and community park as place making approach towards Melana River Sport Arena - Beh, Ming Yi (2022)
In this dissertation, the design strategy of Melana River Park Arena which is proposed in Pulai, adjacent to residential area and Melana River is being discussed. In this project, Melana River Park Arena not only provide sport facilities which could be enjoyed by the community, at the same time, it also plays an important role as mediator between communities and river. Pulai is a suburban area. A town and federal constituency located in Johor, about 25 km or 30 minutes from Johor Bahru city centre. It encompasses a number of neighbourhoods and small towns. Some of these neighbourhoods are located on the outskirts of the area. Thus, they are more peaceful, but further away from urban facilities. Following with results obtained from questionnaires and through site review, insufficient of indoor sport facilities are found in Pulai area. From the questionnaires, aging issues are happening, however health awareness of Pulai residents exist to be low due to insufficient accessible and nearby sport facilities that open to public. Pulai area is a place which showing monotonous architecture dialogue. Proposed Melana River Park Arena however portray place making approach which create place identity for Pulai area. Proposed Melana River Park Arena with social spaces which integrate with propose horizontal park along Melana River not only raise the awareness of public towards Melana River, it also creates a liveable environment for the residents. Also, social engagement of the community could also be enhanced with the propose of Melana River Park Arena which connecting the residents to social spaces in the building and horizontal park along Melana River. All in all, research statement of this dissertation is to propose a sport complex that mediates between community and river in Pulai, where the aim of this dissertation is to formulate a design strategy of sport facilities that promote health, lifestyle and social engagement within the community by integrating and utilizing of Melana River. The research process of this dissertation involves earlier preliminary study of area review and preference study, where questionnaires is being produced and distributed after the preliminary study. Continuously with data analysis and synthesis of the results obtained, design of Melana River Park Arena is proposed followed with design strategy that parallel to the aim and objectives of the project. All in all, through this dissertation, the design strategy of Melana River Park Arena which mediates between communities and river is being discussed.